Proceedings of SPE/PS-CIM/CHOA International Thermal Operations and Heavy Oil Symposium 2005
DOI: 10.2523/97808-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Reservoir Architectures and Steam Chamber Growth at Christina Lake, Alberta, by Using 4D Seismic and Crosswell Seismic Imaging

Abstract: The Christina Lake Thermal Project, located 170 km South of Fort McMurray, Alberta, uses steam-assisted gravity drainage (SAGD) technology to recover bitumen from the McMurray formation. The bitumen reservoir at Christina Lake is approximately 400m deep, and is delineated by over 300 vertical wells and extensive 3D seismic coverage. The McMurray formation can be informally subdivided into three units -Lower, Middle and Upper. The Middle unit contains the major bitumen bearing reservoir, while the Lower unit is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…For example, the steam chamber growth has been observed using 4D and crosswell seismic images at the Christina Lake SAGD project (Zhang et al, 2007). This study clearly showed that the steam chamber growth was not regular.…”
Section: Upscaling Of the Gridmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, the steam chamber growth has been observed using 4D and crosswell seismic images at the Christina Lake SAGD project (Zhang et al, 2007). This study clearly showed that the steam chamber growth was not regular.…”
Section: Upscaling Of the Gridmentioning
confidence: 88%
“…The upscaling was performed using CobraFlow ™ while the SAGD reservoir simulations were performed using PumaFlow ™ . The results were analysed to see if the upscaling factor influences the description of the heterogeneities, a central issue in SAGD production (Birell and Putnam, 2000;Robinson et al, 2005, Zhang et al, 2005Chen et al, 2007;Lerat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Oil rates in excess of 100 m 3 /d have been achieved with 500 m long well pairs. On other fields, 4D seismic results show that fractions of wellbores do not have steam chamber development along their length due to geological heterogeneity (Zhang et al, 2005). Jimenez (2008) reviewed a large database of SAGD operations in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2012) utilized cross-well seismic tomography for monitoring the CO 2 injection process for the Ketzin field in Germany, and showed a clear seismic signal anomaly for the CO 2 injection process. For heavy oil reservoirs, cross-well seismic tomography was used for monitoring the reservoir architecture and steam chamber growth as shown in (Zhang et al, 2007) for the Christina Lake heavy oil reservoir in Canada. The authors indicated that the reservoir heterogeneity may significantly influence the growth process of the steam chamber that was also detected via cross-well seismic data.…”
Section: Introductionmentioning
confidence: 99%